Effects of regular administration of red wine on testicular profile and body weight in adult male experimental mode - Ubi Essien Isaac; Kebe Edet Obeten; Anozeng Oyono Igiri (National Scientific Medical Center, 2021)
Background: The present study determined whether or not the regular intake of red wine causes any significant changes in testicular and body weight parameters, given the simmering controversy over the effect of alcoholic beverages on health system. Methods: Ten male albino Wistar rats -experimental model with average body weight of 140 g were divided into two groups, A and B, (n=5 each). Group A received distilled water being the control while group B was administered a single daily dose of 5 ml/kg body weight of red wine (Carlo Rossi) for 21 days. An electronic weighing scale (G&G® Neuss, Germany) was used to take record of the initial and final body weights. The animals were anesthetized with isoflurane on the 22nd day to enable collection of the testes which were also weighed and thereafter fixed in 10% neutral formalin for routine histological studies. The analysis of variance (ANOVA) was used with the 'R' software to analyze the statistical data, while P<0.05 was taken as the significant value. Results: The micro-anatomical investigation revealed enhanced perfusion of the tissue and normal morphology of the seminiferous tubules with constituent spermatogenic cells at different stages of maturation. The biometric assessment of the organ (testis) weight showed no significant difference; whereas there was a statistically significant increase in the final body weight of the treated-experimental model when compared with the control. Conclusion: The findings indicate that the intake of red wine at the investigated amount may maintain the integrity of the primary reproductive structure and lead to body weight gain in males.